You need to differentiate the given function with respect to x, using the chain rule, such that:

`(u(v(x)))' = u'(v(x))*v'(x)*x'`

Reasoning by analogy yields:

`h'(x) = (e^(2x))'*(2x)' - 3(tan(x^2+1))'(x^2+1)'`

`h'(x) = 2(e^(2x)) - 3(1/(cos^2(x^2+1)))(2x)`

Factoring out 2 yields:

`h'(x) = 2(e^(2x) - (3x)/(cos^2(x^2+1)))`

You should remember that `sec x = 1/(cos x) => sec^2 x = 1/(cos^2 x),` hence, you may use the alternate result substituting `sec^2(x^2+1)` for `1/(cos^2(x^2+1))` such that:

`h'(x) = 2(e^(2x) - (3x)(sec^2(x^2+1)))`

**Hence, evaluating the derivative of the given function yields `h'(x) = 2(e^(2x) - (3x)/(cos^2(x^2+1))) `**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now